A practicum at Davao milk processing plant Malagos, Baguio district, Davao city - Atienza, Julius Steven Antero (2006)
The plant practice held at Davao Milk Processing Plant allowed the proponent to gain knowledge with regard to milk and the several processes involved. The products manufactured in the plant include the pasteurized fresh milk, flavored milk, milk bars, processing line where raw milk is screened and processed. He was also given the chance to get involved in packaging and bottling pasteurized fresh milk and flavored milk. In the laboratory, he was tasked to perform the physic-chemical and microbiological tests for raw milk and liquid milk products as part of the quality control monitoring. He also took part in the monthly inspection in milk collection centers. In the product research and development project, he participated in the sensory evaluation of the new formulated melon and pandan milk bars. In addition to this, he was also involved in the development and formulation of the sterilized evaporated milk. He was exposed to the production of white cheese and pastillas de leche, as well as in the monitoring of the horizontal water circulation retort. He also developed good working ethics with the employees in the plant. He cited problems encountered during his raining and has provided recommendations to improve some operations and product handling in the plant